Medicago truncatula PHO2 genes have distinct roles in phosphorus homeostasis and symbiotic nitrogen fixation - Huertas, Raul; Torres-Jerez, Ivone; Curtin, Shaun J.; Scheible, Wolf; Udvardi, Michael (Frontiers in Plant Science, 2023)
Three PHO2-like genes encoding putative ubiquitin-conjugating E2 enzymes of Medicago truncatula were characterized for potential roles in phosphorous (P) homeostasis and symbiotic nitrogen fixation (SNF). All three genes, MtPHO2A, B and C, contain miR399-binding sites characteristic of PHO2 genes in other plant species. Distinct spatiotemporal expression patterns and responsiveness of gene expression to P- and N-deprivation in roots and shoots indicated potential roles, especially for MtPHO2B, in P and N homeostasis. Phenotypic analysis of pho2 mutants revealed that MtPHO2B is integral to Pi homeostasis, affecting Pi allocation during plant growth under nutrient-replete conditions, while MtPHO2C had a limited role in controlling Pi homeostasis. Genetic analysis also revealed a connection between Pi allocation, plant growth and SNF performance. Under N-limited, SNF conditions, Pi allocation to different organs was dependent on MtPHO2B and, to a lesser extent, MtPHO2C and MtPHO2A. MtPHO2A also affected Pi homeostasis associated with nodule formation. Thus, MtPHO2 genes play roles in systemic and localized, i.e., nodule, P homeostasis affecting SNF.